Keeping the edge : managing defense for the future - Carter, Ashton B.; White, John Patrick, 1937- (BCSIA studies in international security., 2001)
Most national security debates concern the outcomes of policies, neglecting the means by which those policies are implemented. This book argues that although the US military is the finest fighting force in the world, the system that supports it is in disrepair. Operating with Cold War-era structures and practices, it is subject to managerial and organizational problems that increasingly threaten our military's effectiveness. Keeping the Edge goes beyond questions of Pentagon reorganization and weapons procurement to explore how the US defense establishment can improve its readiness, logistics, and ability to attract and retain qualified personnel. It also looks at how the US military can exploit information technology more effectively, improve its intelligence, and counter asymmetric threats. More comprehensive than the usual exhortation to cut waste, fraud, and abuse at the Pentagon, the book in fact recommends changes in many government agencies, not just the Department of Defense. It shows how the US can improve its ability to implement its policies and to anticipate and adapt to a changing and uncertain world.